(untitled) (Actual Problems of Mind, 2021)
This paper is the Ukrainian translation of the first chapter of “The Logic of Scientific Discovery” by K. Popper. The translation was made with an educational purpose: to introduce students to K. Popper’s philosophical views and teach them how to analyze and translate primary sources. The translation was fulfilled as a part of the project held by the Department of Philosophy, aiming to develop the creative potential of the students within the student problem groups and academic clubs at the Kryvyi Rih State Pedagogical University. The translators tried to preserve the original structure and author’s style. This chapter contains essential epistemological ideas of K. Popper’s philosophy: his views on the unreliability of induction as a method of scientific research, the introduction of falsifiability as a criterion of demarcation and the attempt to work out the problem of the ‘empirical basis’. The paper consists of eight sections: (1) the problem of induction, (2) elimination of psychologism, (3) deductive testing of theories, (4) the problem of demarcation, (5) experience as a method, (6) falsifiability as a criterion of demarcation, (7) the problem of ‘empirical basis’, (8) scientific objectivity and subjective conviction. K. Popper thinks it is problematic to justify inductive inference, i.e. the inference that passes from singular statements. Scientists need to work out under what conditions such justification is reliable. The arising problem is known as the problem of induction. According to Popper, a scientist cannot avoid this problem, as the scientific work consists in putting forward and testing theories. The possible way to eliminate it is to develop deductive testing. To accomplish this task, K. Popper develops the procedure of deductive testing of theories. He elaborates falsifiability as a deductive method of testing. Falsifiability means the potential possibility for conclusions and inferences passed from singular statements to be refuted. K. Popper suggests it should be the criterion of demarcation, i.e. the procedure of distinguishing scientific knowledge from non-scientific views, which are called ‘metaphysical’ ones. The feature of scientific knowledge is its objectivity. According to K. Popper, objective knowledge implies inter-subjectively testing. He acknowledges that such testing may last forever, and that also creates a problem. Nevertheless, scientific statements must be capable of being tested.